Cyclic Voltammetry of Ruthenium Complexes for Nonlinear Optics - Mendes, Paulo J. G. (2008)
We report herein the cyclic voltammetry studies of the compounds [RuCp(P_P)(NCSC4H2nNO2)][PF6] (P_P=DPPE, (+)-DIOP; n=1-3) in dichloromethane and acetonitrile. The electronic richness of the organometallic moiety together with the evaluation of the corresponding HOMO-LUMO gaps and correlation with spectroscopic data will be addressed. The overall data will be used in order to give an insight on the SONLO properties of these compounds.